Jo-1 positive paraneoplastic systemic sclerosis in a patient with metastatic melanoma - Figl, Adina; Figl, Robert; Schadendorf, Dirk; Ugurel, Selma (European journal of dermatology, 2006)
A link between systemic sclerosis (SSc) and malignancy is suggested by epidemiological evidence, but the underlying mechanism connecting both diseases has been a source of ongoing controversy. Here, we describe the first case of paraneoplastic SSc secondary to a primarily diagnosed melanoma. Two months after diagnosis of metastatic melanoma, a 40-year-old female presented with high serum titers of antinuclear antibodies (ANA), but no symptoms of autoimmune disease. Five months later, the onset of Raynaud’s phenomenon together with highly positive Jo-1 antibodies was observed. The following clinical course of scleroderma was correlated to melanoma remission and progression. Finally, the patient developed severe pulmonary fibrosis, massive pleural effusion, severe thoracic scleroderma and necrosis of the fingertips, simultaneously with a progression of melanoma to disseminated lymph node metastases and a small brain metastasis. This rare case of SSc concurrent with melanoma suggests that besides other possible mechanisms, paraneoplastic etiology can be responsible for the association between SSc and cancer.